Traumatic Ulnar Artery Pseudoaneurysm Following a Grenade Blast: Report of a Case. Issue 6 (1st June 2015) - Belyayev, Leonid; Rich, Norman M.; McKay, Patricia; Nesti, Leon; Wind, Gary
ABSTRACT: Vascular injuries comprised a small percentage of total injuries requiring medevac in the Iraq and Afghanistan conflicts; however, their impact cannot be overstated. This case highlights an individual who sustained a grenade blast injury leading to hemorrhage, and forearm compartment syndrome. He was initially treated with irrigation and debridement, forearm fasciotomy, and delayed primary closure. The patient developed persistent ulnar neuropathy and hypothenar atrophy despite a normal initial vascular examination. During reconstructive surgery, he was discovered to have a proximal ulnar artery pseudoaneurysm. Upper extremity pseudoaneurysms are a rare sequelae following vascular injury, but have significant consequences for the patient and are identifiable by imaging.